2014
DOI: 10.1002/stem.1573
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 and KDM6A Act as an Epigenetic Switch to Regulate Mesenchymal Stem Cell Lineage Specification

Abstract: The methyltransferase, Enhancer of Zeste homology 2 (EZH2), trimethylates histone 3 lysine 27 (H3K27me3) on chromatin and this repressive mark is removed by lysine demethylase 6A (KDM6A). Loss of these epigenetic modifiers results in developmental defects. We demonstrate that Ezh2 and Kdm6a transcript levels change during differentiation of multipotential human bone marrow-derived mesenchymal stem cells (MSC). Enforced expression of Ezh2 in MSC promoted adipogenic in vitro and inhibited osteogenic differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
228
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(261 citation statements)
references
References 49 publications
26
228
1
Order By: Relevance
“…Thus, overexpression of EZH2 protein in human MSCs impairs their potential to differentiate to osteoblasts, in part by producing increased levels of H3K27me3 at regulatory regions of bone-related target genes, including Runx2 and osteocalcin/ Bglap (34). In agreement with this report, CDK1-dependent phosphorylation of EZH2 at residue Thr-487, which prevents formation of an active PRC2 complex, promotes differentiation of human MSCs to osteoblasts (35).…”
supporting
confidence: 86%
“…Thus, overexpression of EZH2 protein in human MSCs impairs their potential to differentiate to osteoblasts, in part by producing increased levels of H3K27me3 at regulatory regions of bone-related target genes, including Runx2 and osteocalcin/ Bglap (34). In agreement with this report, CDK1-dependent phosphorylation of EZH2 at residue Thr-487, which prevents formation of an active PRC2 complex, promotes differentiation of human MSCs to osteoblasts (35).…”
supporting
confidence: 86%
“…More recently, enforced expression of EZH2 in human bone marrow-derived MSC promoted adipogenesis in vitro and inhibited osteogenic differentiation potential in vitro and in vivo [25]. Conversely, inhibition of EZH2 enzymatic activity and knockdown of EZH2 gene expression inhibited adipogenesis and promoted osteogenic differentiation by MSC [25].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, inhibition of EZH2 enzymatic activity and knockdown of EZH2 gene expression inhibited adipogenesis and promoted osteogenic differentiation by MSC [25]. EZH2 has been reported to be regulated through phosphorylation at Thr 487 by cyclin-dependent kinase 1 (CDK1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the transcription factors and signaling molecules, the Jumonji-domain-containing histone demethylases have been shown to be of great importance in the control of osteogenic differentiation (20,21). Nucleolar protein 66 (NO66) is a Jumonji C-domain-containing protein and is conserved in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Bone formation and growth are also controlled by a broad signaling network including IGF, bone morphogenetic protein (BMP), and members of the Wnt family (11)(12)(13)(14)(15). Previous studies showed that dysregulation of these signaling molecules results in abnormal bone growth (16)(17)(18)(19).In addition to the transcription factors and signaling molecules, the Jumonji-domain-containing histone demethylases have been shown to be of great importance in the control of osteogenic differentiation (20,21). Nucleolar protein 66 (NO66) is a Jumonji C-domain-containing protein and is conserved in eukaryotes.…”
mentioning
confidence: 99%